Cutaneous angiomyolipoma - Singh Kulwant; Pai Radha; Kini Hema; Kini Ullal (Wolters Kluwer Medknow Publications, 2009)
Cutaneous angiomyolipomas are rare. We report a case in a 45-year-old male with a well circumscribed lesion located on the chin. This lesion, probably hamartomatous in nature, differs from renal angiomyolipoma in terms of nonassociation with tuberous sclerosis, circumscription, and male predominance. Another characteristic feature is the absence of epithelioid cells. Differential diagnosis includes angiolipoma, angioleiomyoma, hemangioma, and myolipoma. It is distinguished from the abovementioned entities by the presence of a combination of thick-walled blood vessels, smooth muscle, and fat.